Jerusalem : city of longing - Goldhill, Simon (Cambridge, Mass. Belknap Press of Harvard University Press, 2008)
Jerusalem is the site of some famous religious monuments in the world, from the Dome of the Rock to the Church of the Holy Sepulchre to the Western Wall of the Temple. This work takes you on a tour through the history of this image-filled and ideology-laden city--from the bedrock of the Old City to the towering roofs of the Holy Sepulchre.
Keywords: Jerusalem -- Description and travel. Jerusalem -- Buildings, structures, etc. Jerusalem -- Ethnic relations